Silicon Nanowires Based DNA Biosensor - Uda, Hashim, Prof. Dr.; Siti Fatimah, Abdul Rahman; Muhammad Emi Azri, Shohini (Malaysia Association of Research Scientists (MARS), 2010)
Prof. Dr. Uda Hashim and his team won bronze at Malaysia Technology Expo 2010 (MTE 2010), 4th - 6th February 2010 at Putra World Trade Centre (PWTC), Kuala Lumpur. MTE 2010 organized by MARS and PROTEMP Exhibitions Sdn. Bhd.